2009
DOI: 10.1089/jmf.2008.0270
|View full text |Cite
|
Sign up to set email alerts
|

Regular Tart Cherry Intake Alters Abdominal Adiposity, Adipose Gene Transcription, and Inflammation in Obesity-Prone Rats Fed a High Fat Diet

Abstract: Obesity, systemic inflammation, and hyperlipidemia are among the components of metabolic syndrome, a spectrum of phenotypes that can precede the development of type 2 diabetes and cardiovascular disease. Animal studies show that intake of anthocyanin-rich extracts can affect these phenotypes. Anthocyanins can alter the activity of tissue peroxisome proliferator-activated receptors (PPARs), which affect energy substrate metabolism and inflammation. However, it is unknown if physiologically relevant, anthocyanin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
88
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(101 citation statements)
references
References 48 publications
8
88
1
1
Order By: Relevance
“…Cyanidin is the major anthocyanin in tart cherries (Seeram et al 2001a) followed by flavan-3-ols and flavonols (Bhagwat et al 2014). Studies using cell lines, animal models, and humans demonstrated that the phytochemicals found in tart cherry confer health benefits by inducing cell-cycle arrest and apoptosis in precancerous and cancer cells (Kang et al 2003;Bobe et al 2006;Martin and Wooden 2012;Sehitoglu et al 2014), decreasing triglyceride and total cholesterol levels (Seymour et al 2008), reducing inflammation (Seeram et al 2001b;Tall et al 2004;Seymour et al 2009;Ou et al 2012), and decreasing oxidative stress (Kim et al 2005;Traustadottir et al 2009). Furthermore, a study by Kirakosyan showed that cherry anthocyanins accumulated in the brain of young rats after 3 weeks of feeding with either 1 or 10 % tart cherry-supplemented diets in a dose-dependent manner (Kirakosyan et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Cyanidin is the major anthocyanin in tart cherries (Seeram et al 2001a) followed by flavan-3-ols and flavonols (Bhagwat et al 2014). Studies using cell lines, animal models, and humans demonstrated that the phytochemicals found in tart cherry confer health benefits by inducing cell-cycle arrest and apoptosis in precancerous and cancer cells (Kang et al 2003;Bobe et al 2006;Martin and Wooden 2012;Sehitoglu et al 2014), decreasing triglyceride and total cholesterol levels (Seymour et al 2008), reducing inflammation (Seeram et al 2001b;Tall et al 2004;Seymour et al 2009;Ou et al 2012), and decreasing oxidative stress (Kim et al 2005;Traustadottir et al 2009). Furthermore, a study by Kirakosyan showed that cherry anthocyanins accumulated in the brain of young rats after 3 weeks of feeding with either 1 or 10 % tart cherry-supplemented diets in a dose-dependent manner (Kirakosyan et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, PPAR-␣ mRNA was increased 2.7-fold. It is interesting that the cherry treatment had no effect on body weight gain in the earlier study using lean rats, but in the study with the rat model prone to obesity and inflammation there was a significant reduction in body weight and abdominal fat mass [11,12]. The results suggest that tart cherry intake resulted in reduced inflammation in retroperitoneal fat, though specificity of the action to cell type within the adipose tissue was not determined [11,12].…”
Section: In Vivo Studiesmentioning
confidence: 95%
“…A subsequent study from Seymour et al showed whole tart cherry powder reduced circulating plasma levels of tumor necrosis factor alpha (TNF-␣) and IL-6 after 90 days of treatment in obesity-prone Zucker rats fed a high fat diet [12]. The authors observed plasma reductions of 44% in IL-6 and 40% in TNF-␣ after 90 days.…”
Section: In Vivo Studiesmentioning
confidence: 96%
See 2 more Smart Citations